The Normative Impact of CPA Firms, Professional Organizations, and State Boards on Accounting Ethics Education - Misiewicz, Kevin M. (2007)
Accounting educators are in the midst of creating new opportunities for students to enhance their abilities to recognize ethical dilemmas, establish criteria by which to make ethical decisions, and establish support mechanisms and strategies to facilitate their ethical decision-making. CPA firms, professional organizations and state boards of accountancy are co-operating to increase requirements for ethics education for candidates taking the CPA exam. The current situation is confusing and sub-optimal regarding the use of precious learning time in college programs. A new dialogue between the three stakeholders, creative learning approaches, and additional resources can lead to a more consistent and optimal learning paradigm regarding the ethics education of accountants. Research evaluating the effectiveness of various approaches is needed to effectively apply limited resources in an area critical to the reputation capital of the accounting profession.
Keywords: Students; University; exam; CPA; Education; Accounting; Ethics